2020
DOI: 10.1186/s12859-020-03856-0
|View full text |Cite
|
Sign up to set email alerts
|

High quality genome assemblies of Mycoplasma bovis using a taxon-specific Bonito basecaller for MinION and Flongle long-read nanopore sequencing

Abstract: Background Implementation of Third-Generation Sequencing approaches for Whole Genome Sequencing (WGS) all-in-one diagnostics in human and veterinary medicine, requires the rapid and accurate generation of consensus genomes. Over the last years, Oxford Nanopore Technologies (ONT) released various new devices (e.g. the Flongle R9.4.1 flow cell) and bioinformatics tools (e.g. the in 2019-released Bonito basecaller), allowing cheap and user-friendly cost-efficient introduction in various NGS workflows. While singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Additionally, whether antimicrobial resistance is associated with specific genetic strains is not clear, as some studies observed no association between genetic subtypes based on the polC subtyping scheme [ 11 ], while others did for lincosamides and macrolides [ 9 ]. With whole genome sequencing (WGS) becoming more popular and commercially available for identification and strain typing [ 16 , 17 , 18 , 19 ], it might be helpful to determine whether phenotypic antimicrobial susceptibility patterns are associated with genomic clusters of M. bovis . Therefore, the objective of the present study was to compare the antimicrobial susceptibility results of M. bovis isolates obtained from veal calf, conventional dairy and beef herds, and to explore the association of antimicrobial resistance (AMR) with specific M. bovis genomic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, whether antimicrobial resistance is associated with specific genetic strains is not clear, as some studies observed no association between genetic subtypes based on the polC subtyping scheme [ 11 ], while others did for lincosamides and macrolides [ 9 ]. With whole genome sequencing (WGS) becoming more popular and commercially available for identification and strain typing [ 16 , 17 , 18 , 19 ], it might be helpful to determine whether phenotypic antimicrobial susceptibility patterns are associated with genomic clusters of M. bovis . Therefore, the objective of the present study was to compare the antimicrobial susceptibility results of M. bovis isolates obtained from veal calf, conventional dairy and beef herds, and to explore the association of antimicrobial resistance (AMR) with specific M. bovis genomic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, both read and consensus accuracy are limited by the organisms chosen for model training, and they are drastically reduced when the basecaller is used for less frequently sequenced microbial species [140] . This issue can be addressed by developing more custom-trained basecallers, built-on taxon-specific training data so that the users can choose which basecaller most closely matches the organisms present in their samples [140] , [141] . Sequencing data throughput by single flow cell is also continuously improving, enabling the detection and sequencing of DNA/RNA from microbes even when present in very low abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, hospital environments such as NICUs are known to house several related species concurrently, and finding ways to accurately detect different related bacteria at species- or even strain-level is important for effective surveillance and diagnosis in healthcare settings (29,30). Recently developed tools like the Bonito basecaller promise to take on some of nanopore’s main limitations and may turn high-accuracy long-read sequencing into a reality within the next years (31).…”
Section: Discussionmentioning
confidence: 99%